Human BBB-on-a-chip reveals barrier disruption, endothelial inflammation, and T cell migration under neuroinflammatory conditions - Nair, Arya Lekshmi; Groenendijk, Linda; Overdevest, Roos; Fowke, Tania M.; Annida, Rumaisha; Mocellin, Orsola; de Vries, Helga E.; Wevers, Nienke R. (Frontiers in Molecular Neuroscience, 2023)
The blood-brain barrier (BBB) is a highly selective barrier that ensures a homeostatic environment for the central nervous system (CNS). BBB dysfunction, inflammation, and immune cell infiltration are hallmarks of many CNS disorders, including multiple sclerosis and stroke. Physiologically relevant human in vitro models of the BBB are essential to improve our understanding of its function in health and disease, identify novel drug targets, and assess potential new therapies. We here present a microfluidic human BBB platform that allows parallel culture of 40 BBBs-on-chips. Primary human brain microvascular endothelial cells (HBMECs) form a lumenized vessel against a collagen-I extracellular matrix gel and form a tight monolayer, evidenced by expression of relevant adherensand tight junction proteins and low permeability to small molecule sodium fluorescein. Inflammation was mimicked by exposing the model to increasing concentrations of the pro-inflammatory cytokines tumor necrosis factor alpha (TNFα) and interleukin-1 beta (IL-1β). In response to these triggers, the BBBs-on-chips showed decreased transendothelial electrical resistance (TEER), increased permeability to sodium fluorescein, and aberrant cell morphology in a concentration-dependent manner. Moreover, we observed increased expression of endothelial cell adhesion molecules and concomitant monocyte adhesion. Immune cell migration was studied by perfusing T cells through the lumen of the BBBs-on-chips. T cells extravasated from the inflamed blood vessels and migrated towards a C-X-C Motif Chemokine Ligand 12 (CXCL12) gradient. T cell adhesion was significantly reduced and a trend towards decreased migration was observed in presence of Natalizumab, an antibody drug that blocks very late antigen-4 (VLA-4) and is used in the treatment of multiple sclerosis. In conclusion, we demonstrate a high-throughput microfluidic model of the human BBB that can be used to model neuroinflammation and assess anti-inflammatory and barrier-restoring interventions to fight neurological disorders.